Numerical simulations of a swimmer’s head and cap wearing different types of goggles - Marinho, D.A. (2021)
The aim of this study was to analyse the effect of swimming goggles on swimming hydrodynamics by numerical simulations. An elite swimmer volunteered for this research. The swimmer's head was scanned both without goggles, and while wearing 3 different types of goggles (Nikko, Ankor and Swedish). Numerical simulations were conducted at 2 m/s with the Fluent code. The condition without goggles showed the highest viscous drag (1.65 N), followed by the Ankor (1.64 N), Swedish (1.63 N) and Nikko (1.62 N) goggles, respectively. The highest pressure drag was found in the situation without goggles (11.34 N), followed by the Ankor (10.87 N), Nikko (10.78 N) and Swedish (10.20 N) goggles. The condition without goggles presented the highest total drag (12.99 N), followed by the Ankor (12.52 N), Nikko (12.40 N) and Swedish (11.83 N) goggles. Thus, Swedish goggles yields the best hydrodynamics, followed by the Nikko and Ankor goggles and lastly without goggles. Thus, goggles minimise the swimmer's drag comparing to not wearing any. The design of the goggles may impose varying drag forces and therefore it is advised to use goggles at least in competition.